The practice of supply chain management in Capricorn District with particular reference to Aganang Municipality - Rabodiba, Malola Japhta (My University, 2010)
The study investigated the supply-chain management practices in Capricorn District Municipality and Aganang Local Municipality. The study also looked at the implementation of the supply-chain management policies in the Capricorn District and Aganang Local municipalities. The study critically analysed the practice of supply-chain management in Capricorn and Aganang municipalities and the challenges faced by these municipalities in terms of procurement and supply-chain management in general. The findings of the study will assist government with interventions that are necessary for the improvement of the supply-chain management practices in the local sphere of government. The study also investigated and analysed possible non-compliance with supply-chain management legislation and policies, and purchasing and tender irregularities in Capricorn District and Aganang Local municipalities. It also investigated whether the evaluation and adjudication of bids were in accordance with the applicable legislation. The study further recommended possible strategies and mechanisms to improve procurement and supply-chain management to prevent fraud and corruption.
Thesis (MPA) --University of Limpopo, 2006.
Keywords: Not available